AN ANALYSIS OF THE RESPONSIBILITY FOR ZERO WASTE - Buble Ivana; Rolph Schneider Daniel; Samec Niko; Kokalj, Filip (Journal of Energy Technology, 2024)
European Union Directive 2008/98/EC sets the priority hierarchy of the prevention of waste, re-using waste, recycling waste, waste recovery, and waste disposal. Although every one of us is in daily contact with waste, we do not have the knowledge that can lead us to the sound management of waste from the beginning, before products are identified as waste. Zero waste is a fundamental concept of the sustainable community of the future. It is a phrase frequently used by politicians seeking to upgrade the municipal solid waste management systems in their communities. In this manner, the responsibility of zero waste is given to the waste management process instead of to householders. Householders then equate waste prevention with recycling and the proper waste management of the collectors, public services, or waste management company. In reality, zero waste starts with each one of us at home. Households should aim to reduce consumption and undertake repairs to extend the life span of products. Behaviour change can only start with knowledge. In reality, waste prevention does not include recycling. Recycling leads to a combined reduction of waste brought to landfill and raw material extraction. The present paper evaluates household waste to clarify the facts. It analyses the composition of three streams: municipal solid waste, separately collected packaging waste, and bulky waste in different regions of Slovenia. The research defines waste into five different categories. The first category is waste that can and should be avoided. The second category is waste that can be re‐used. Further on, the research expands by researching the market of the third category that defines recyclables, which waste can be recycled; the last two categories are the waste that we are fighting with at the end of the waste management process, either to make it to the waste‐to‐energy process or to comply with landfill restrictions. At the end of the research, we summarize the situation of household waste in 2018. Our goal is to reduce the quantity of waste, making only waste that can be recycled. If we consider waste prevention to be a fight against waste, we can put our plan in place by taking the first step: getting to know our enemy.